If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+8)=8x+5-4x+27
We move all terms to the left:
4(x+8)-(8x+5-4x+27)=0
We add all the numbers together, and all the variables
4(x+8)-(4x+32)=0
We multiply parentheses
4x-(4x+32)+32=0
We get rid of parentheses
4x-4x-32+32=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 7+5x=4+9x | | -35=1x-4x+10(1x+1)-2x-(x+1) | | 56=8(h+2)-24 | | 2(x+5)-8+3x=12+3x-2 | | -149=-5-9x | | 1=g-1.2 | | 5(t+5)-(-10)=50 | | 6+7x=7=6x | | 3y+5=14=2 | | 10x-2.66666667-4x=6x | | 2c=17.3 | | 9/10+3/5n=-23/10+1/5n | | -2(s+11)=4 | | 5x-6+3x+14+2x=18 | | x/⁷=6 | | -3(x-1)-5x+2=11-4(2x+3) | | 3-f=-10 | | -104=-4(2-3x) | | -10+7n=-2(6-3n)+3n | | 5m*2-22+8=0 | | X=5/6v+8;v | | 12=24n-4(6n-2) | | m^2-196=0 | | 3m^2-6m=24 | | (2x9)+(3x-1)=180 | | 3(x+6)-2(3x-4)=-50 | | 1-c=-10 | | 4(z+1)=36 | | 41-2n=-5(2n-8)* | | 2(w-3)-5=4(w-1) | | 5x+12=4(2x-9) | | -3(x+6)2(3x-4)=-50 |